Methodology of fire resistance evaluation of steel columns with fire structural protection, located on the perimeter of the premises - Zhamoydik Сергей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
Purpose. The paper is devoted to engineering method for structural steel columns with fire protec-tion for two- and three-sided fire exposure fire resistance design, with regard to the warming up of steel caused by the destruction of adjacent walling. Methods. Based on full-scale fire research the method of steel columns with structural fire protection warming up was improved, set around a premise (building). Findings. The method of steel structures warming up, using the elementary heat balance mathematical model was developed. The technique was worked out and full-scale fire research of structural fire protection and adjacent structures mutual interaction was conducted. Research application field. The obtained experimental and theoretical study data could be used in fire resistance design of steel structures with structural fire protection. Conclusions. The steel warming up factor for columns with structural fire protection due to the adjacent walling destruction was revealed.